2017
DOI: 10.1016/j.nicl.2017.04.013
|View full text |Cite
|
Sign up to set email alerts
|

Shared and disorder-specific task-positive and default mode network dysfunctions during sustained attention in paediatric Attention-Deficit/Hyperactivity Disorder and obsessive/compulsive disorder

Abstract: Patients with Attention-Deficit/Hyperactivity Disorder (ADHD) and obsessive/compulsive disorder (OCD) share problems with sustained attention, and are proposed to share deficits in switching between default mode and task positive networks. The aim of this study was to investigate shared and disorder-specific brain activation abnormalities during sustained attention in the two disorders. Twenty boys with ADHD, 20 boys with OCD and 20 age-matched healthy controls aged between 12 and 18 years completed a function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
30
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 133 publications
(302 reference statements)
2
30
0
Order By: Relevance
“…The increased level of omission errors in those with OCD only is indicative of a deficit in sustained attention (50). Whilst the higher level of omission errors reported here contrasts with previous work where OCD (in the absence of comorbidities) was associated with a decrease in omission and an increase in commission errors (22), it is in line with studies showing poorer sustained attention in OCD (51,52).…”
Section: Discussionsupporting
confidence: 77%
“…The increased level of omission errors in those with OCD only is indicative of a deficit in sustained attention (50). Whilst the higher level of omission errors reported here contrasts with previous work where OCD (in the absence of comorbidities) was associated with a decrease in omission and an increase in commission errors (22), it is in line with studies showing poorer sustained attention in OCD (51,52).…”
Section: Discussionsupporting
confidence: 77%
“…Findings of decreased activation in these regions extend previous findings in ADHD during TD ( Ortiz et al, 2015 , Rubia et al, 2009 ), by showing that deficits are shared with patients with OCD during this task. Interestingly, we have previously shown that IFG underactivation is disorder-specific in ADHD relative to OCD during inhibitory and attentional control ( Norman et al, 2016 , Norman et al, 2017 , Rubia et al, 2010 ). Current findings are in line with suggestions that inhibitory control and TD are mediated by neuroanatomically overlapping but functionally dissociable fronto-striatal neural circuits ( Fineberg et al, 2014 ), and suggest that IFG underactivation in ADHD relative to OCD is task-specific to the contexts of inhibitory and attentional control, but not the context of TD.…”
Section: Discussionmentioning
confidence: 95%
“…In the brain, we hypothesised shared underactivation in both disorders relative to controls in striatal, DLPFC and cerebellar regions previously implicated in ADHD ( Carlisi et al, 2016 , Hart et al, 2013 , Norman et al, 2016 ) and OCD ( Carlisi et al, 2017a , Carlisi et al, 2017b , Carlisi et al, in press ; Norman et al, 2016 ; Rubia et al, 2010 , Rubia et al, 2011 ). We, however, hypothesised more prominent or disorder-specific abnormalities in OCD patients in VMPFC/OFC ( Carlisi et al, 2017b , Menzies et al, 2008 , Norman et al, 2016 , Norman et al, 2017 ), and larger or disorder-specific underactivation in IFG in ADHD patients ( Noreika et al, 2013 , Norman et al, 2016 , Norman et al, 2017 , Rubia et al, 2009 , Rubia et al, 2010 ). Data have been published in other forms elsewhere, although in this paper we provide the novel comparison between controls, patients with ADHD and patients with OCD ( Carlisi et al, 2016 , Carlisi et al, 2017b , Chantiluke et al, 2014 , Christakou et al, 2011 , Rubia et al, 2009 ).…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…, in gray matter structure(3,5,(67)(68)(69), during symptom provocation(63,70,71), and across multiple cognitive and decision-making tasks in OCD(3-5, 72, 73). Moreover, many resting-state, structural and functional abnormalities within these regions are shared with unaffected relatives of patients with OCD (26,64,65,68,71,74,75), and are OCD-specific relative to disorders such as attention deficit/hyperactivity disorder and anxiety disorders(3,42,54,72,73). The current findings provide further evidence for cross-modal abnormalities in cinguloopercular and orbito-striato-thalamic brain networks in OCD(3,6), which may be endophenotypes for the disorder(68).…”
mentioning
confidence: 99%